Anticorrosive paint for outdoor metal components
By combining modified calcium sulfate whiskers with aqueous epoxy resin emulsion and other raw materials, the shortcomings of anticorrosion coatings in acid and alkali resistance are solved, and the acid and alkali resistance and corrosion resistance of the paint film are significantly improved. It is suitable for a variety of outdoors Metal component.
Patent Information
- Application Number
- CN202411542619.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-27
AI Technical Summary
Existing anticorrosion coatings have shortcomings in their acid and alkali resistance, and it is difficult to effectively protect outdoor metal components from corrosion from acid and alkali environment.
Modified calcium sulfate whiskers are combined with aqueous epoxy resin emulsion, amino resin and other raw materials to enhance the effect of modified calcium sulfate whiskers through siliconoxy grafting and polymerization, and improve the impact resistance and pull-out of the paint film. Strength and acid and alkali resistance.
It significantly improves the acid and alkali resistance and corrosion resistance of the paint film, so that it can show better mechanical properties and adhesion on outdoor metal components such as stainless steel, aluminum alloy, galvanized plate, etc., to meet market demand.
Smart Images

Figure BDA0005113121060000051 
Figure BDA0005113121060000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water-based coatings, and more specifically, to an anti-corrosion coating for outdoor metal components. Background Art
[0002] Outdoor metal components are exposed to the natural environment for a long time. They are easily corroded by external factors such as the atmosphere, water, and chemicals, which causes the performance of metal components to decline, shorten their lifespan, and may also pose safety hazards. Among the many anti-corrosion technical means for metal components, the use of anti-corrosion coatings is one of the effective protective methods to reduce or delay the corrosion of metal components. Anti-corrosion coatings have the advantages of convenient construction, strong adaptability, and low price, and have been widely used. Existing anti-corrosion coatings often use water-based epoxy resin emulsions as raw materials, and film-forming aids, catalysts, wetting agents, defoaming agents, leveling agents and other additives are added to the raw materials, and the raw materials are mixed to obtain anti-corrosion coatings. Although the anti-corrosion coating has good water resistance, its acid and alkali resistance is poor and needs to be further improved. Summary of the invention
[0003] In order to improve the acid and alkali resistance of the anti-corrosion coating, the present application provides an anti-corrosion coating for outdoor metal components, which adopts the following technical solution: An anticorrosive coating for outdoor metal components, which is mainly made of the following raw materials in parts by weight: 90-110 parts of waterborne epoxy resin emulsion, 9-11 parts of amino resin, 2-4 parts of film-forming aid, 0.3-0.8 parts of catalyst, 2-4 parts of modified calcium sulfate whisker, 1-3 parts of organic bentonite, 1-2 parts of substrate wetting agent, 0.2-0.5 parts of adhesion promoter, 0.2-0.5 parts of anti-flash agent, 0.3-0.8 parts of defoaming agent, 0.3-0.8 parts of leveling agent, and 60-70 parts of deionized water; The modified calcium sulfate whisker is obtained by treating the calcium sulfate whisker with 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, trifluoroethyl acrylate and 4-acrylamidobenzoic acid ethyl ester.
[0004] The anti-corrosion coating for outdoor metal components of this application, through the mutual coordination between raw materials, makes the impact strength of the paint film>70cm, the pulling strength>5MPa, the neutral salt spray resistance>55d, the acid resistance>40d, and the alkali resistance>45d, showing the advantages of strong mechanical properties, high adhesion, good acid and alkali resistance, and good anti-corrosion effect, meeting market demand. At the same time, the paint film obtained by the anti-corrosion coating of this application has a flat, beautiful, smooth, and uniform appearance, which is easy to construct and is suitable for the protection of outdoor metal components such as stainless steel, aluminum alloy, galvanized sheet, copper sheet, copper alloy, cast iron, etc., expanding the scope of application.
[0005] Adding waterborne epoxy resin emulsion and amino resin to the raw materials of the anticorrosive coating makes the paint film have good basic properties. Adding calcium sulfate whiskers and organic bentonite not only plays a filling role, but also can increase the bonding force and integrity between the raw materials, so that the paint film shows better mechanical properties, adhesion, acid and alkali resistance and anticorrosion effect. Further, the calcium sulfate whiskers are also modified, and a large number of active groups such as siloxy, anhydride, ester, fluorine, phenyl, and amide groups are introduced on the surface of the calcium sulfate whiskers to enhance the interaction between the modified calcium sulfate whiskers and the raw materials, improve the use effect of the modified calcium sulfate whiskers, improve the impact resistance, pull-off strength, neutral salt spray resistance, acid resistance, and alkali resistance of the paint film, enhance the overall performance of the paint film, and make the anticorrosive coating show better comprehensive performance.
[0006] Optionally, the modified calcium sulfate whisker is prepared by the following method: T1. Add calcium sulfate whiskers to ethanol and mix, then add 3-(methacryloyloxy)propyltrimethoxysilane, and stir for 1-3 hours to obtain a premixed solution; T2. Mix the premixed liquid, 2-methylene succinic anhydride, trifluoroethyl acrylate, and ethyl 4-acrylamidobenzoate, add peroxide, stir for 2-4 hours, filter, wash, and dry to obtain modified calcium sulfate whiskers.
[0007] Optionally, the weight ratio of the calcium sulfate whisker, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, trifluoroethyl acrylate, 4-acrylamidobenzoic acid ethyl ester, and peroxide is (9-11):(2-4):(0.5-1.5):(0.5-1.5):(0.5-1.5):(0.05-0.2).
[0008] By adopting the above technical scheme, 3-(methacryloyloxy)propyltrimethoxysilane is firstly grafted on the surface of calcium sulfate whiskers by using siloxy groups, and carbon-carbon double bonds are introduced. Then, 2-methylenesuccinic anhydride, trifluoroethyl acrylate, and 4-acrylamidoethylbenzoate are grafted on the surface of calcium sulfate whiskers by using polymerization reaction. The preparation method of the present application completes the grafting of calcium sulfate whiskers in steps, ensures the grafting amount on the surface of calcium sulfate whiskers, is also convenient for the preparation of calcium sulfate whiskers, enhances the use effect of modified calcium sulfate whiskers, and improves the overall performance of the paint film.
[0009] Optionally, the peroxide is one or more of di-tert-butyl peroxide, tert-amyl peroxide pivalate, dibenzoyl peroxide, benzoic acid peroxide, and tert-butyl perbenzoate.
[0010] By adopting the technical scheme, the peroxide is optimized, which facilitates the selection of the peroxide, and di-tert-butyl peroxide, tert-amyl peroxide pivalate, dibenzoyl peroxide, benzoic acid peroxide, and tert-butyl perbenzoate can all release free radicals, and initiate and promote polymerization reactions, thereby ensuring the smooth grafting of organic matter and also ensuring the stability and use effect of the preparation of the modified calcium sulfate whisker.
[0011] Optionally, in the method for preparing modified calcium sulfate whiskers, the weight ratio of calcium sulfate whiskers to ethanol is (9-11):(80-120).
[0012] Optionally, the calcium sulfate whiskers have an average diameter of 1-3 μm and an average length of 20-50 μm.
[0013] By adopting the above technical scheme, the average diameter and average length of calcium sulfate whiskers are optimized to ensure that calcium sulfate whiskers have a good aspect ratio and enhance the effect of calcium sulfate whiskers on the mechanical properties and anticorrosive properties of coatings. In multiple embodiments, the average diameter of calcium sulfate whiskers is 2 μm and the average length is 30 μm. It can also set the average diameter to 1 μm, 1.5 μm, 2.5 μm, 3 μm as needed, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable. It can also set the average length to 20 μm, 25 μm, 35 μm, 40 μm, 45 μm, 50 μm, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0014] Optionally, the water-based epoxy resin emulsion is water-based epoxy resin emulsion EPIKOTE 3520-WY-55A; and the amino resin is amino resin CYMEL325.
[0015] By adopting the above technical scheme, the water-based epoxy resin emulsion and the amino resin are optimized, which facilitates the selection of the water-based epoxy resin emulsion and the amino resin, and ensures the stability and quality of the anti-corrosion coating performance.
[0016] Optionally, the film-forming aid is one or more of film-forming aid HY-12C, film-forming aid NX 795, film-forming aid DALPAD292, and film-forming aid OE 400.
[0017] By adopting the above technical solution, the film-forming aid is optimized, which facilitates the selection of the film-forming aid. Moreover, the film-forming aid can effectively improve the film-forming property of the anti-corrosion coating, enhance the flexibility and weather resistance of the paint film, and ensure the acid and alkali resistance and anti-corrosion effect of the anti-corrosion coating.
[0018] Optionally, the catalyst is one or more of catalyst CYCAT 4040, catalyst CYCAT 4045, catalyst CYCAT6020, and catalyst CYCAT 296-10.
[0019] By adopting the above technical solution, the catalyst is optimized, which facilitates the selection of the catalyst. Moreover, the catalyst can promote the reaction, increase the curing rate of the anti-corrosion coating and the hardness of the paint film, and enhance the anti-corrosion performance of the anti-corrosion coating.
[0020] Optionally, the substrate wetting agent is one or more of substrate wetting agent TEGO 4100, substrate wetting agent TEGO 245, substrate wetting agent HY-408, and substrate wetting agent Dynol 607; The adhesion promoter is one or more of adhesion promoter LD-157, adhesion promoter XH-168, adhesion promoter Z-6040, and adhesion promoter YB-201D.
[0021] By adopting the above technical solution, the substrate wetting agent and adhesion promoter are optimized, which facilitates the selection of the substrate wetting agent and adhesion promoter. Moreover, through the mutual cooperation between the substrate wetting agent and the adhesion promoter, the film peeling phenomenon can be reduced, and the adhesion and durability of the paint film can be enhanced.
[0022] Optionally, the anti-flash embroidery agent is one or more of anti-flash embroidery agent HX-1126, anti-flash embroidery agent THIF-3118, anti-flash embroidery agent CK34, and anti-flash embroidery agent R-726; The defoamer is one or more of the defoamer AKN-3801, the defoamer TEGO 830, the defoamer BYK 024, and the defoamer HY-024; The leveling agent is one or more of the leveling agent TEGO 410, the leveling agent BYK-333, the leveling agent BYK-310, and the leveling agent EFKA-FL3777.
[0023] By adopting the above technical solution, the anti-flash embroidery agent, defoaming agent and leveling agent are optimized, which is convenient for the selection of anti-flash embroidery agent, defoaming agent and leveling agent. Moreover, through the mutual cooperation of anti-flash embroidery agent, defoaming agent and leveling agent, the rust of the paint film can be reduced, the appearance of the paint film can be kept flat, beautiful, smooth and uniform, and the quality of the paint film can be improved.
[0024] Optionally, a method for preparing an anti-corrosion coating for outdoor metal components comprises the following steps: The anti-corrosion coating is obtained by mixing water-based epoxy resin emulsion, amino resin, film-forming aid, catalyst, modified calcium sulfate whisker, organic bentonite, substrate wetting agent, adhesion promoter, anti-flash agent, defoaming agent, leveling agent and deionized water.
[0025] In summary, this application has at least the following beneficial effects: 1. The anti-corrosion coating for outdoor metal components of the present application adds modified calcium sulfate whiskers and organic bentonite to the raw materials, and utilizes the synergistic effect between them to greatly enhance the bonding force and integrity between the raw materials, not only making the paint film appearance flat, beautiful, smooth and uniform, but also making the paint film exhibit better mechanical properties, adhesion, acid and alkali resistance and anti-corrosion effects, and the impact resistance of the paint film is greater than 70cm, the pulling strength is greater than 5MPa, the neutral salt spray resistance is greater than 55d, the acid resistance is greater than 40d, and the alkali resistance is greater than 45d, which improves the comprehensive performance of the paint film and ensures the quality of the anti-corrosion coating. It is suitable for the protection of outdoor metal components such as stainless steel, aluminum alloy, galvanized sheet, copper sheet, copper alloy, cast iron, etc., and meets market demand.
[0026] 2. The modified calcium sulfate whisker preparation method of the present application uses siloxy groups to graft 3-(methacryloyloxy)propyltrimethoxysilane on the surface of the calcium sulfate whisker, and then uses polymerization reaction to graft 2-methylenesuccinic anhydride, trifluoroethyl acrylate, and 4-acrylamidoethylbenzoate on the surface of the calcium sulfate whisker. The preparation method of the present application is simple and convenient to prepare, and it also ensures the use effect of the modified calcium sulfate whisker and improves the comprehensive performance of the paint film. DETAILED DESCRIPTION
[0027] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0028] Preparation Example Preparation Example 1 A modified calcium sulfate whisker is prepared by the following method: T1. Add 10 g of calcium sulfate whiskers to 100 g of ethanol at a rotation speed of 400 r / min and stir for 5 min. Then add 3 g of 3-(methacryloyloxy)propyltrimethoxysilane and stir for 2 h to obtain a premixed solution.
[0029] Among them, the calcium sulfate whiskers have an average diameter of 2 μm and an average length of 30 μm, and are selected from Jinan Xinquan Chemical Technology Co., Ltd.
[0030] T2. At a rotation speed of 400 r / min, add 1 g of 2-methylene succinic anhydride, 1 g of trifluoroethyl acrylate, and 1 g of ethyl 4-acrylamidobenzoate to the premixed solution obtained in step T1, and stir for 2 min. Then add 0.1 g of peroxide and stir for 3 h. Then filter, wash, and dry to obtain modified calcium sulfate whiskers.
[0031] Wherein, the peroxide is di-tert-butyl peroxide.
[0032] Preparation Example 2 A modified calcium sulfate whisker is prepared by the following method: T1. Add 9 g of calcium sulfate whiskers to 80 g of ethanol at a rotation speed of 400 r / min and stir for 5 min. Then add 2 g of 3-(methacryloyloxy)propyltrimethoxysilane and stir for 1 h to obtain a premixed solution.
[0033] Among them, the calcium sulfate whiskers have an average diameter of 2 μm and an average length of 30 μm, and are selected from Jinan Xinquan Chemical Technology Co., Ltd.
[0034] T2. At a rotation speed of 400 r / min, add 1.5 g of 2-methylene succinic anhydride, 1.5 g of trifluoroethyl acrylate, and 0.5 g of ethyl 4-acrylamidobenzoate to the premixed solution obtained in step T1, and stir for 2 min. Then add 0.2 g of peroxide and stir for 2 h. Then filter, wash, and dry to obtain modified calcium sulfate whiskers.
[0035] Wherein, the peroxide is di-tert-butyl peroxide.
[0036] Preparation Example 3 A modified calcium sulfate whisker is prepared by the following method: T1. Add 11 g of calcium sulfate whiskers to 120 g of ethanol at a rotation speed of 400 r / min and stir for 5 min. Then add 4 g of 3-(methacryloyloxy)propyltrimethoxysilane and stir for 3 h to obtain a premixed solution.
[0037] Among them, the calcium sulfate whiskers have an average diameter of 2 μm and an average length of 30 μm, and are selected from Jinan Xinquan Chemical Technology Co., Ltd.
[0038] T2. At a rotation speed of 400 r / min, add 0.5 g of 2-methylene succinic anhydride, 0.5 g of trifluoroethyl acrylate, and 1.5 g of ethyl 4-acrylamidobenzoate to the premixed solution obtained in step T1, and stir for 2 min. Then add 0.05 g of peroxide and stir for 4 h. Then filter, wash, and dry to obtain modified calcium sulfate whiskers.
[0039] Wherein, the peroxide is di-tert-butyl peroxide. Example
[0040] Table 1 Amount of each raw material used in anticorrosive coatings (unit: ×10g) Example 1 An anti-corrosion coating for outdoor metal components, the raw materials and raw material ratios of which are shown in Table 1.
[0041] Among them, the water-based epoxy resin emulsion is water-based epoxy resin emulsion EPIKOTE 3520-WY-55A; the amino resin is amino resin CYMEL325; the film-forming aid is film-forming aid HY-12C; the catalyst is catalyst CYCAT 4040; the organic bentonite is organic bentonite BENTONE SD-1; the substrate wetting agent is substrate wetting agent TEGO 4100; the adhesion promoter is adhesion promoter LD-157; the anti-flash embroidery agent is anti-flash embroidery agent HX-1126; the defoaming agent is defoaming agent AKN-3801; the leveling agent is leveling agent TEGO 410; and the modified calcium sulfate whiskers are prepared by the method of Preparation Example 1.
[0042] A method for preparing an anti-corrosion coating for outdoor metal components comprises the following steps: At a speed of 800 r / min, deionized water and amino resin were added to the water-based epoxy resin emulsion and stirred for 5 minutes. Then, film-forming aid, catalyst, substrate wetting agent, adhesion promoter, anti-flash agent, defoaming agent, and leveling agent were added and stirred for 5 minutes. Then, modified calcium sulfate whiskers and organic bentonite were added and stirred for 10 minutes to obtain an anti-corrosion coating.
[0043] Example 2 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that the raw material ratio of the anti-corrosion coating is different, and the raw material ratio is shown in Table 1.
[0044] Example 3 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that the raw material ratio of the anti-corrosion coating is different, and the raw material ratio is shown in Table 1.
[0045] Example 4 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that the source of the modified calcium sulfate whiskers in the raw materials of the anti-corrosion coating is different, and the modified calcium sulfate whiskers are prepared by the method of Preparation Example 2.
[0046] Example 5 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that the source of the modified calcium sulfate whiskers in the raw materials of the anti-corrosion coating is different, and the modified calcium sulfate whiskers are prepared by the method of Preparation Example 3.
[0047] Comparative Example Comparative Example 1 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that, in the raw materials of the anti-corrosion coating, modified calcium sulfate whiskers and organic bentonite are replaced with equal amounts of water-based epoxy resin emulsion.
[0048] Comparative Example 2 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that, in the raw materials of the anti-corrosion coating, modified calcium sulfate whiskers and organic bentonite are replaced with equal amounts of calcium sulfate whiskers.
[0049] Comparative Example 3 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that an equal amount of organic bentonite is used to replace modified calcium sulfate whiskers in the raw materials of the anti-corrosion coating.
[0050] Comparative Example 4 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that an equal amount of calcium sulfate whiskers is used to replace modified calcium sulfate whiskers in the raw materials of the anti-corrosion coating.
[0051] Comparative Example 5 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that, in the raw materials of the anti-corrosion coating, in the preparation method of modified calcium sulfate whiskers, an equal amount of 2-methylenesuccinic anhydride is used to replace trifluoroethyl acrylate and 4-acrylamidobenzoic acid ethyl ester.
[0052] Comparative Example 6 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that, in the raw materials of the anti-corrosion coating, in the preparation method of modified calcium sulfate whiskers, an equal amount of trifluoroethyl acrylate is used to replace 4-acrylamidobenzoic acid ethyl ester.
[0053] Comparative Example 7 An anti-corrosion coating for outdoor metal components, which differs from Example 1 in that, in the raw materials of the anti-corrosion coating, in the preparation method of modified calcium sulfate whiskers, an equal amount of 4-acrylamidobenzoic acid ethyl ester is used to replace trifluoroethyl acrylate.
[0054] Performance Testing The anti-corrosion coatings obtained in Examples 1-5 and Comparative Examples 1-7 were respectively taken as samples, and the following performance tests were performed on the samples. The test results are shown in Table 2.
[0055] Among them, according to GB / T1732-2020 "Determination of Impact Resistance of Paint Films", the impact resistance of the samples is tested, and the greater the impact resistance, the better the mechanical properties of the paint film.
[0056] According to GB / T5210-2006 "Pull-off adhesion test for paints and varnishes", the pull-off strength of the sample is tested, and the greater the pull-off strength, the better the adhesion of the paint film.
[0057] According to GB / T1771-2007 “Determination of neutral salt spray resistance of paints and varnishes”, the neutral salt spray resistance of the samples was tested.
[0058] According to GB / T9274-1988 “Determination of resistance of paints and varnishes to liquid media”, the acid and alkali resistance of the samples were tested.
[0059] Among them, the resistant liquid medium used for acid resistance is a hydrochloric acid aqueous solution with a mass concentration of 5% and a temperature of 23°C; the resistant liquid medium used for alkali resistance is a sodium hydroxide aqueous solution with a mass concentration of 5% and a temperature of 23°C.
[0060] Table 2 Test results Test items Impact strength / (cm) Pull-out strength / (MPa) Neutral salt spray resistance / (d) Acid resistance / (d) Alkali resistance / (d) Example 1 75 5.9 60 45 52 Example 2 73 5.7 58 44 50 Example 3 72 5.8 57 43 51 Example 4 73 5.8 59 43 51 Example 5 74 5.7 57 44 50 Comparative Example 1 43 4.7 34 23 28 Comparative Example 2 58 4.4 46 34 38 Comparative Example 3 55 5.1 43 32 36 Comparative Example 4 62 4.9 49 37 41 Comparative Example 5 65 5.2 51 38 44 Comparative Example 6 69 5.6 54 40 45 Comparative Example 7 68 5.6 55 41 46 As can be seen from Table 2, the paint film obtained by the anti-corrosion coating of the present application has high impact strength and tensile strength, with an impact strength of 72-75 cm and a tensile strength of 5.7-5.9 MPa, showing high mechanical properties and adhesion. It also has high resistance to neutral salt spray, acid and alkali, with a neutral salt spray resistance of 57-60 d, an acid resistance of 43-45 d, and an alkali resistance of 50-52 d, showing high acid and alkali resistance and anti-corrosion effect, and can meet market demand.
[0061] Comparative Examples 1-4 are compared. In the raw materials of the anti-corrosion coating of Comparative Example 1, calcium sulfate whiskers and organic bentonite were not added; in the raw materials of the anti-corrosion coating of Comparative Example 2, calcium sulfate whiskers were added; in the raw materials of the anti-corrosion coating of Comparative Example 3, organic bentonite was added. It can be seen that adding organic bentonite alone to the anti-corrosion coating can improve the pull-off strength, but adding calcium sulfate whiskers alone can reduce the pull-off strength. Moreover, adding organic bentonite or calcium sulfate whiskers alone can increase the impact resistance, acid and alkali resistance and anti-corrosion effect. Combined with Comparative Example 4, calcium sulfate whiskers and organic bentonite were added to the raw materials of the anti-corrosion coating of Comparative Example 4. It can be seen that, further, adding organic bentonite and calcium sulfate whiskers to the anti-corrosion coating at the same time, and utilizing their mutual cooperation, can significantly improve the impact resistance, neutral salt spray resistance, acid resistance and alkali resistance without affecting the pull-off strength.
[0062] Comparative Example 4 and Comparative Example 5 are compared. Calcium sulfate whiskers are added to the raw materials of the anticorrosive coating of Comparative Example 4; calcium sulfate whiskers treated with 3-(methacryloyloxy)propyltrimethoxysilane and 2-methylenesuccinic anhydride are added to the raw materials of the anticorrosive coating of Comparative Example 5. It can be seen that the modification of calcium sulfate whiskers can improve the compatibility between calcium sulfate whiskers and raw materials, and significantly improve the adhesion of the paint film. At the same time, it can also improve the mechanical properties, acid and alkali resistance, and anticorrosion effect of the paint film. Combined with Comparative Examples 6-7 and Example 1, the raw materials of the anti-corrosion coating in Comparative Example 6 were added with calcium sulfate whiskers treated with 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, and trifluoroethyl acrylate; the raw materials of the anti-corrosion coating in Comparative Example 7 were added with calcium sulfate whiskers treated with 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, and 4-acrylamidobenzoic acid ethyl ester; the raw materials of the anti-corrosion coating in Example 1 were added with calcium sulfate whiskers treated with 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, trifluoroethyl acrylate, and 4-acrylamidobenzoic acid ethyl ester. From this, it can be seen that in the contact of 3-(methacryloyloxy)propyltrimethoxysilane and 2-methylenesuccinic anhydride for grafting calcium sulfate whiskers, further, trifluoroethyl acrylate and 4-acrylamidoethylbenzoate are grafted at the same time, and the synergistic effect therebetween can be utilized to further improve the use effect of the modified calcium sulfate whiskers, and improve the impact strength, tensile strength, neutral salt spray resistance, acid resistance, and alkali resistance, enhance the overall performance of the paint film, and make the anti-corrosion coating show better comprehensive performance and use effect.
[0063] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. An anticorrosive coating for outdoor metal components, characterized in that: The invention is mainly made of the following raw materials in parts by weight: 90-110 parts of waterborne epoxy resin emulsion, 9-11 parts of amino resin, 2-4 parts of film-forming aid, 0.3-0.8 parts of catalyst, 2-4 parts of modified calcium sulfate whisker, 1-3 parts of organic bentonite, 1-2 parts of substrate wetting agent, 0.2-0.5 parts of adhesion promoter, 0.2-0.5 parts of anti-flash agent, 0.3-0.8 parts of defoaming agent, 0.3-0.8 parts of leveling agent and 60-70 parts of deionized water; The modified calcium sulfate whisker is obtained by treating the calcium sulfate whisker with 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, trifluoroethyl acrylate and 4-acrylamidobenzoic acid ethyl ester.
2. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The modified calcium sulfate whisker is prepared by the following method: T1. Add calcium sulfate whiskers to ethanol and mix, then add 3-(methacryloyloxy)propyltrimethoxysilane, and stir for 1-3 hours to obtain a premixed solution; T2. Mix the premixed liquid, 2-methylene succinic anhydride, trifluoroethyl acrylate, and ethyl 4-acrylamidobenzoate, add peroxide, stir for 2-4 hours, filter, wash, and dry to obtain modified calcium sulfate whiskers.
3. The anti-corrosion coating for outdoor metal components according to claim 2, characterized in that: The weight ratio of the calcium sulfate whisker, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methylenesuccinic anhydride, trifluoroethyl acrylate, 4-acrylamidoethylbenzoate and peroxide is (9-11):(2-4):(0.5-1.5):(0.5-1.5):(0.5-1.5):(0.05-0.2).
4. The anti-corrosion coating for outdoor metal components according to claim 2, characterized in that: The peroxide is one or more of di-tert-butyl peroxide, tert-amyl peroxide pivalate, dibenzoyl peroxide, benzoic acid peroxide, and tert-butyl perbenzoate.
5. The anti-corrosion coating for outdoor metal components according to claim 2, characterized in that: The calcium sulfate whiskers have an average diameter of 1-3 μm and an average length of 20-50 μm.
6. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The water-based epoxy resin emulsion is water-based epoxy resin emulsion EPIKOTE 3520-WY-55A; the amino resin is amino resin CYMEL325.
7. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The film-forming aid is one or more of the film-forming aid HY-12C, the film-forming aid NX 795, the film-forming aid DALPAD 292, and the film-forming aid OE 400.
8. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The catalyst is one or more of catalyst CYCAT 4040, catalyst CYCAT 4045, catalyst CYCAT 6020, and catalyst CYCAT 296-10.
9. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The substrate wetting agent is one or more of substrate wetting agent TEGO 4100, substrate wetting agent TEGO 245, substrate wetting agent HY-408, and substrate wetting agent Dynol 607; The adhesion promoter is one or more of adhesion promoter LD-157, adhesion promoter XH-168, adhesion promoter Z-6040, and adhesion promoter YB-201D.
10. The anti-corrosion coating for outdoor metal components according to claim 1, characterized in that: The anti-flash embroidery agent is one or more of anti-flash embroidery agent HX-1126, anti-flash embroidery agent THIF-3118, anti-flash embroidery agent CK34, and anti-flash embroidery agent R-726; The defoamer is one or more of the defoamer AKN-3801, the defoamer TEGO 830, the defoamer BYK 024, and the defoamer HY-024; The leveling agent is one or more of the leveling agent TEGO 410, the leveling agent BYK-333, the leveling agent BYK-310, and the leveling agent EFKA-FL3777.
Citation Information
Patent Citations
High-temperature resisting fireproof coating and preparation method thereof
CN107236423A
Modified calcium sulphate crystal whisker as well as preparation method and application thereof
CN108003386A
Steel structure fireproof coating containing calcium sulfate whiskers
CN109321097A
Aqueous epoxy zinc-enriched paint and preparation method therefor
CN110643260A
Concrete for prefabricated part as well as preparation method and application of concrete
CN118324470A
